Pima County COVID-19 vaccine solutions dashboard project: lessons learned - Tina Damalas; Eamon Penney; Theresa Cullen; Aaron Dibner-Dunlap; Cecelia English; Jacob Gomez; Amanda Sapp; Sara Selig; Staci Sutermaster (Frontiers in Digital Health, 2024)
Recent improvements in the accessibility of mapping tools and an increased recognition of the importance of leveraging data to inform public health operations has led to enthusiasm among public health departments to rapidly evolve their ability to analyze and apply data to programs. As the COVID-19 pandemic made evident, many health department data systems have been neglected for decades and data literacy among staff low. Significant federal dollars have been allocated to local health departments to modernize health systems. This case study recounts the effort to equip the Pima County Health Department with a highly sophisticated “COVID-19 Vaccines Solutions Dashboard” in 2021–2022, quantifying community vulnerability in the midst of the COVID-19 pandemic and shares key successes and challenges in process and outcomes that can guide other such dashboard initiatives. The experience informed the development of Pima' County Health Department's Data & Informatics Team as well as efforts to cultivate a more robust data culture throughout the department. Many health departments around the United States are in a similar position, and these lessons learned are widely applicable.